Conventional MRI-based subchondral trabecular biomarkers as predictors of knee osteoarthritis progression: data from the Osteoarthritis Initiative - Pishgar, Farhad; Guermazi, Ali; Roemer, Frank; Link, Thomas M.; Demehri, Shadpour (European Radiology, 2020)
Objectives: To evaluate the reliability and validity of measuring subchondral trabecular biomarkers in “conventional” intermediate-weighted (IW) MRI sequences and to assess the predictive value of biomarker changes for predicting near-term symptomatic and structural progressions in knee osteoarthritis (OA). Methods: For this study, a framework for measuring trabecular biomarkers in the proximal medial tibia in the “conventional” IW MRI sequence was developed. The reliability of measuring these biomarkers (trabecular thickness [cTbTh], spacing [cTbSp], connectivity density [cConnD], and bone-to-total volume ratio [cBV/TV]) was evaluated in the Bone Ancillary Study (within the Osteoarthritis Initiative [OAI]). The validity of these measurements was assessed by comparing to “apparent” biomarkers (from high-resolution steady-state MRI sequence) and peri-articular bone marrow density (BMD, from dual-energy X-ray absorptiometry). The association of these biomarker changes from baseline to 24 months (using the Reliable Change Index) with knee OA progression was studied in the FNIH OA Biomarkers Consortium (within the OAI). Pain and radiographic progression were evaluated by comparing baseline WOMAC pain score and radiographic joint space width with the 24-to-48-month scores/measurements. Associations between biomarker changes and these outcomes were studied using logistic regression adjusted for the relevant covariates. Results: With acceptable reliability, the cTbTh and cBV/TV, but not cTbSp or cConnD, were modestly associated with the “apparent” biomarkers and peri-articular BMD (β: 1.10 [95% CI: 0.45–1.75], p value: 0.001 and β: 3.69 [95% CI: 2.56–4.83], p value: < 0.001, respectively). Knees with increased cTbTh had higher (OR: 1.44 [95% CI: 1.03–2.02], p value: 0.035) and knees with decreased cTbTh (OR: 0.69 [95% CI: 0.49–0.95], p value: 0.026) or decreased cBV/TV (OR: 0.67 [95% CI: 0.48–0.93], p value: 0.018) had lower odds of experiencing OA pain progression over the follow-ups. Conclusions: Measurement of certain “conventional” MRI-based subchondral trabecular biomarkers has high reliability and modest validity. Though modest, there are significant associations between these biomarker changes and knee OA pain progression up to 48-month follow-up. Key Points: • Despite the lower spatial resolution than what is required to accurately study the subchondral trabecular microstructures, the “conventional” IW MRI sequences may retain adequate information that allows quantification of trabecular microstructure biomarkers. • Subchondral trabecular biomarkers obtained from “conventional” IW MRI sequences (i.e., cTbTh, cTbSp, and cBV/TV) are reliable and valid measures of trabecular microstructure changes compared to those from “apparent” trabecular biomarkers (from the FISP MRI sequence) and peri-articular BMD (from DXA). • Increased trabecular thickness and bone-to-total ratio (cTbTh and cBV/TV, obtained from “conventional” IW MRI sequences) from baseline to 24-month visits may be associated with higher odds of knee OA pain progression over 48 months of follow-up.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Biomarkers; Knee joint; Magnetic resonance imaging; Osteoarthritis; knee